Expanding the Genetic Code of Yeast for Incorporation of Diverse Unnatural Amino Acids via a Pyrrolysyl-tRNA Synthetase/tRNA Pair - Hancock, Susan M. (American Chemical Society, 2010)
[Image: see text] We report the discovery of a simple system through which variant pyrrolysyl-tRNA synthetase/tRNA(CUA)(Pyl) pairs created in Escherichia coli can be used to expand the genetic code of Saccharomyces cerevisiae. In the process we have solved the key challenges of producing a functional tRNA(CUA)(Pyl) in yeast and discovered a pyrrolysyl-tRNA synthetase/tRNA(CUA)(Pyl) pair that is orthogonal in yeast. Using our approach we have incorporated an alkyne-containing amino acid for click chemistry, an important post-translationally modified amino acid and one of its analogs, a photocaged amino acid and a photo-cross-linking amino acid into proteins in yeast. Extensions of our approach will allow the growing list of useful amino acids that have been incorporated in E. coli with variant pyrrolysyl-tRNA synthetase/tRNA(CUA)(Pyl) pairs to be site-specifically incorporated into proteins in yeast.